Changes in physical activity and weight status of Chinese children: A retrospective longitudinal study - Pengyu Deng; Noriko Ichinoseki-Sekine; Liangfu Zhou; Hisashi Naito (Japanese Society of Physical Fitness and Sports Medicine, 2016)
The aims of this study were to describe longitudinal changes in objectively measured physical activity (PA) in Chinese children and to investigate the associations of such changes with weight status, gender, and day of the week. This study was conducted on 50 boys and 43 girls. Children underwent measurements in 2011 (age 7-8 years, 2nd grade) and in 2014 (age 10-11 years, 5th grade). The children were divided into: normal weight (NW) or overweight/obese (OW/OB) groups based on weight status recorded in 2014. PA was quantified by steps measured using a uniaxial accelerometer, then total PA time and time spent performing moderate to vigorous PA (≥ 3 METs) were analyzed separately for weekdays and weekends. The daily PA outcomes and normalized PA outcomes per hour (steps, total PA time, and moderate to vigorous PA) declined with age in the OW/OB group on weekends for boys and on both weekdays and weekends for girls (p < 0.05). But no change was observed in the NW group of boys and girls. The percentages of achieving the global recommendations by WHO also declined with age in the OW/OB group for boys on weekdays (p < 0.05). Moreover, they had significantly less percentages of achieving the WHO recommendations than that of the NW group for boys on both weekdays and weekends in 2014 (p < 0.05). Our findings suggest that longitudinal changes in PA, predominantly in the quantity and intensity of activity, are related to weight status in children. Prevention of this decline in PA among children in OW/OB children, particularly on weekends for boys and on both weekdays and weekends for girls may be a suitable health promotion target.